Cardanol na alimentação de codornas de corte reprodutoras - Rocha, Amanda Karen Santos (2021)
The objective of this work was to evaluate the inclusion of cardanol in the diet of quail breeders on egg performance and quality. 300 European dams with 32 weeks of age were used, distributed in a completely randomized design consisting of 5 treatments and 6 replicates of ten birds, with an experimental unit found of 8 required and 2 males. The treatments consisted of rations with cardanol levels 0.00; 0.25; 0.50; 0.75 and 1.00%. Productive performance, egg quality and reproductive performance were obtained. There was a reduction in the performance of the matrices with the inclusion of 1.00% of cardanol compared to the control treatment, while the egg weight and mass were lower in the treatments with 0.75% and 1.00% of cardanol. respectively. In terms of egg quality, it was observed that, in relation to the control treatment, there was a decrease in specific density and an increase in yolk color, percentage, color and TBARS value in all treatments with cardanol. The inclusion of 0.50% cardanol decreased the percentage of albumen and increased the percentage of yolk, while the shell thickness decreased from 0.75% and the lipid oxidation of the yolk was higher at the level of 1.00%. In the incubation parameters, it was observed that in relation to the control treatment, the weight of the incubated eggs and the weight of the chicks at birth were lower in the 0.75 and 1.00% inclusion treatments, respectively, with a significant linear reduction for both parameters as the inclusion increased. In the evaluation of the performance of the progeny, it was found that the weight of the chicks at 7 days of age, coming from the sows fed with ration containing 1.00% of heated cardanol, was lower in relation to the broiler chicks fed with control ration. It is concluded that the inclusion of cardanol in the feed did not present benefits for the productive, reproductive performance and egg quality.